2013
DOI: 10.1021/pr400753f
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the N-Linked Glycoproteome of Human Spermatozoa

Abstract: N-Linked glycosylation, a type of post-translational modification, plays important roles in cell-cell recognition, adhesion, and interactions. Although N-linked glycosylated proteins in sperm are known to be important for gamete binding, little is known about the composition of these proteins, particularly glycosylation sites, in humans. In the present study, the use of glyco-FASP, coupled with the tandem mass spectrometry (MS/MS) method, led to the identification of 554 N-glycosylation sites and 297 N-glycosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…The dual use of a 30 kDa cut-off filter as a sample cleaner device and as a "proteomic reactor" allowed proper separation of peptides and, at the same time, an increase in the activity of soluble salivary proteases. Thus, we provided the proof-of-concept of a novel peptidomic approach, the endoProteo-FASP, to understand the dynamics of the salivary peptidome, making the most of saliva's own protease pool and avoiding the use of synthetic peptides and exogenous proteases, as previously reported in the literature [12,[15][16][17][18][19][20][21][22]27]. Additionally, our work confirmed the utility of the combination of the ammonium bicarbonate extraction method with sample filtration in order to enrich salivary peptides, as reported previously by our group [28].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The dual use of a 30 kDa cut-off filter as a sample cleaner device and as a "proteomic reactor" allowed proper separation of peptides and, at the same time, an increase in the activity of soluble salivary proteases. Thus, we provided the proof-of-concept of a novel peptidomic approach, the endoProteo-FASP, to understand the dynamics of the salivary peptidome, making the most of saliva's own protease pool and avoiding the use of synthetic peptides and exogenous proteases, as previously reported in the literature [12,[15][16][17][18][19][20][21][22]27]. Additionally, our work confirmed the utility of the combination of the ammonium bicarbonate extraction method with sample filtration in order to enrich salivary peptides, as reported previously by our group [28].…”
Section: Discussionmentioning
confidence: 93%
“…For instance, an N-glyco-FASP approach was developed to enrich N-glycopeptides, retrieving over 6000 N-glycosylation motifs in proteins from mouse brain, kidney, liver, heart and plasma [18]. Posterior studies were performed following the same approach in other biological samples such as mouse microglial cells [19], human spermatozoa [20] and supernatants of cultured breast cancer cell lines [21]. The combination of FASP with sizeexclusion chromatography was also performed to map another posttranslational modification, the phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…PTMs increase the protein complexity of the sample to be analyzed. Several studies applied complementary methods for sperm protein separation and performed proteomic analysis to identify proteins with PTMs such as phosphorylation [76], S-nitrosylation [77], SUMOylation [78], N-glycosylation [79] or lysine-acetylation [80].…”
Section: Advances In Sperm Proteomicsmentioning
confidence: 99%
“…The sperm surface is coated with carbohydrate‐rich molecules that form a thick glycocalyx . N‐Linked glycans, an important constituent of sperm glycocalyx, has an essential role in sperm–egg interaction . A recent study has shown that human sperm binding is mediated by the sialyl–Lewis x oligosaccharide moiety .…”
Section: Ylp12 Peptide Sequencementioning
confidence: 99%